Magnesium sulfate enhances exercise performance and manipulates dynamic changes in peripheral glucose utilization - Cheng, S. M.; Yang, L. L.; Chen, S. H.; Hsu, M. H.; Chen, I. J.; Cheng, F. C. (European Journal of Applied Physiology, 2010)
The effect of magnesium supplementation on exercise performance remains controversial. In the present study, the effects of magnesium sulfate on exercise performance and blood glucose metabolism were examined. In order to provide a non-invasive measure of continuous exercise, we developed an auto-blood sampling system was coupled to a microdialysis analyzer to detect the dynamic changes in glucose metabolism in conscious and freely moving gerbils subjected to forced swimming. Gerbils were pretreated with saline or magnesium sulfate (90 mg kg-1, ip) 30 min before exercise. The duration times were significantly increased by 71% in the magnesium sulfate-treated groups (p < 0.01) when compared with those in the control. Another group of gerbils were subjected to blood sampling assay. A catheter was implanted in the jugular vein of each gerbil for collecting blood samples by the computer-aided blood sampler. The basal levels of plasma glucose, lactate, and magnesium were 6,245 ± 662, 1,067 ± 309, and 590 ± 50 µM, respectively, with no significant difference between groups. Plasma glucose, lactate, and magnesium levels increased to 134 and 204%, 369 and 220%, and 155 and 422% of basal levels during swimming in both the control and magnesium sulfate-treated groups, respectively (p < 0.05). Pretreatment with magnesium sulfate elevated glucose and magnesium levels to 175 and 302% of the basal levels (p < 0.05), respectively, whereas pretreatment with magnesium sulfate reduced the lactate levels 150% of the basal level (p < 0.05) during swimming. Furthermore, the magnesium levels increased to about 152-422% of basal levels during forced swimming and the recovery period (p < 0.05). The present study demonstrates that magnesium sulfate improved the duration time of forced swimming exercise. In addition, magnesium raised glucose levels and attenuated lactate levels during forced swimming. These results indicate that positive effects of magnesium supplementation may contribute to the enhancement of exercise performance in athletes.